Dynamics and Fluctuations in Biomedical Photonics XX 2023
DOI: 10.1117/12.2650582
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of human cerebral fluids measured by near-infrared spectroscopy

Abstract: Obtaining parameters that characterize cerebral fluid interactions in the human brain is of high interest particularly as regards studies of the glymphatic system and in relation to neurodegeneration diseases. Near-infrared spectroscopy (NIRS) based techniques commonly measure cerebral hemodynamics using a combination of wavelengths approximately between 650 nm and 950 nm, where light is to a lesser amount attenuated by water, enabling light to reach the brain. By adding a wavelength that is dominantly absorbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
1
1
0
Order By: Relevance
“…We validated the Monro-Kellie doctrine phenomenon in mice during BP lowering procedures using fNIRS. In our previous study on human cerebral fluid concentration using fNIRS 12 , we also found the same phenomenon about Monro-Kellie doctrine. Thus, fNIRS has potential as a bed-side device to monitor Monro-Kellie doctrine phenomenon for patients.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…We validated the Monro-Kellie doctrine phenomenon in mice during BP lowering procedures using fNIRS. In our previous study on human cerebral fluid concentration using fNIRS 12 , we also found the same phenomenon about Monro-Kellie doctrine. Thus, fNIRS has potential as a bed-side device to monitor Monro-Kellie doctrine phenomenon for patients.…”
Section: Resultssupporting
confidence: 81%
“…Previously, we measured human cerebral fluid concentrations using fNIRS and the results support the Monro-Kellie doctrine 12,13 . Then, we were interested in studying this doctrine further in mice during blood pressure lowering treatment because the physiological response due to cerebral autoregulation provides a good scenario.…”
Section: Introductionmentioning
confidence: 66%